PENGARUH GAYA HIDUP, FITUR, DESAIN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG - Estri Dwi Handayani; Heny Kurnianingsih, S.E.,M.M (MANAJEMEN DEWANTARA, 2021)
Research to determine and analyze the effect of lifestyle, features, design and product quality on purchasing decisions for Samsung smartphones in Surakarta, both simultaneously and partially. The population of Samsung smartphone users in Surakarta. The sample used is Non Probability Sampling, with purposive sampling technique, a total of 100 samples. Observation data collection, questionnaires and literature study. Data analysis with data instrument test. Data processing uses classical assumption test, model test and influence test between x and y. The study states that lifestyle, design, features and product quality obtained a value of Fcount 98.127 <from Ftable value of 2.46 so that there is an influence between lifestyle variables, design, features and product quality that affect the decision to purchase Samsung smartphones in Surakarta simultaneously. Lifestyle variables obtained t-value 5.422 and p-value 0.000> 0.05, which means that lifestyle has a significant positive effect on purchasing decisions. For the design, the regression value obtained t-count value of 5.190 and p-value of 0.000> 0.05 means that the design has a positive and significant effect on purchasing decisions. While the feature variable obtained a t-count value of 2.086 with a p-value of 0.000> 0.40 which means that features have a positive and significant effect on purchasing decisions, and the product quality variable is obtained by a regression value of the t-count equation of 2.525 with a p-value of 0.013> 0.40 which this means that product quality has a positive and significant effect on purchasing decisions for Samsung smartphones in Surakarta.